Pengaruh Opini Audit dan Temuan Audit BPK terhadap Kinerja Pemerintah Daerah pada Kabupaten/Kota di Provinsi Jawa Timur - Rollis Ayu Ditasari; Muhamad Agus Sudrajat (INVENTORY: JURNAL AKUNTANSI, 2020)
This study aims to prove empirically the effect of the Audit Opinion variable and BPK Audit Finding Variables on the Performance of Local Government in districts / cities in East Java Province. This study used purposive sampling with 148 samples obtained from districts / cities in East Java Province. Data testing was performed using: 1) Descriptive statistical test, 2) Classical assumption test, 3) Multiple linear regression and 4) Hypothesis test of the R Determination Coefficient and t test. The researcher processed the research data using special software, namely IBM SPSS Statistics 16. The results of the analysis of this study were 1) Audit Opinion has no effect on the performance of local governments in East Java. This is supported by the tcount value of -1.276 and table of -1.655 so that the tcount value is smaller than the t table value. The significance value is 0.204> 0.05, thus H1 is rejected. 2) BPK Audit findings affect the performance of local governments in East Java. This is supported by the tcount value of -2.267 and the t table of -1.655 so that the tcount value is smaller than the t table value. The significance value is 0.562< 0.05, thus H2 is accepted.Keyword; Audit Opinion; BPK Audit Findings and East Java Regional Government Performance.